Maximum permisible temperature deviations for thermolabile medicines - SILGADO, R; JIMÉNEZ, MJ; FERRARI, JM; HERREROS DE TEJADA, A (Ars Pharmaceutica (Internet), 2006)
Thermolabile medicines are especially susceptible to storage errors in both transportation and storage at pharmaciesand dispensing units in different clinical centres. The objective of this study was to produce a quick consultative tablethat gives information on stability times at room temperature and procedures when freezing of medicines occur, fordrugs included in hospital pharmacotherapeutic guides. The table was produced from information provided by manufacturinglaboratories.